Islam Dan Transformasi Budaya Keluarga Pemulung Di Kota Administratif Jember: Islam and the Cultural Transformation of Scavenger Families in Jember Administrative City - Munif Widodo (Fenomena, 2003)
The socioeconomic marginalization of urban scavenger communities often obscures the role of Islamic values in shaping their daily lives, creating a disconnect between religious doctrine and cultural practice. This study is grounded in the broader discourse on Islam and cultural transformation, particularly among informal-sector workers in Indonesia’s urban poor. The research aims to examine how Islamic perspectives are integrated into the cultural practices of scavenger families in Jember and to identify which cultural aspects hinder or support Islamic development programs. A qualitative-descriptive method was employed, involving observations, interviews, and documentation with 50 respondents from the scavenger community. The findings reveal that most scavengers are economic migrants whose daily activities are dominated by survival needs, while religious practices remain minimal and ceremonial. Although they view poverty as divine destiny, they maintain strong work ethics and optimism. However, formal worship and communal religious participation are limited by time constraints and low religious literacy. The study concludes that Islamic development programs for scavenger families must consider their economic realities and culturally specific understandings of religion, and recommends context-sensitive dakwah approaches that integrate material and spiritual empowerment Marginalisasi sosial-ekonomi komunitas pemulung perkotaan sering mengaburkan peran nilai-nilai Islam dalam kehidupan sehari-hari, menciptakan kesenjangan antara doktrin agama dan praktik budaya. Penelitian ini berlandaskan wacana tentang Islam dan transformasi budaya, khususnya pada sektor informal di kalangan masyarakat miskin perkotaan Indonesia. Penelitian bertujuan mengkaji bagaimana perspektif keislaman menjadi unsur pola budaya keluarga pemulung di Kota Jember dan segi-segi budaya mana yang menjadi kendala atau pendukung program pengembangan Islam. Metode deskriptif kualitatif digunakan melalui observasi, wawancara, dan dokumentasi terhadap 50 responden dari komunitas pemulung. Hasil penelitian menunjukkan bahwa mayoritas pemulung adalah urbanis yang didorong faktor ekonomi, sehingga aktivitas ekonomi mendominasi keseharian mereka, sementara aktivitas keagamaan relatif kecil dan bersifat seremonial. Meskipun mereka memandang kemiskinan sebagai takdir Tuhan, mereka tetap memiliki etos kerja tinggi dan optimisme. Namun, ibadah formal dan partisipasi keagamaan sangat terbatas karena kesibukan dan rendahnya literasi agama. Penelitian menyimpulkan bahwa program pengembangan Islam bagi keluarga pemulung harus mempertimbangkan realitas ekonomi dan pemahaman budaya mereka, serta merekomendasikan pendekatan dakwah kontekstual yang mengintegrasikan pemberdayaan material dan spiritual.